2008
DOI: 10.3174/ajnr.a1129
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Cerebrovascular Reserve Measured by Acetazolamide-Challenged Dynamic CT Perfusion in Ischemic Adult Moyamoya Disease: Initial Experience with Angiographic Correlation

Abstract: BACKGROUND AND PURPOSE:CT perfusion is a much more readily accessible imaging method to assess cerebral hemodynamic status than single-photon emission CT. We prospectively assessed quantitative cerebrovascular reserve by using acetazolamide (ACZ)-challenged CT perfusion for evaluating hemodynamic impairment in ischemic adult Moyamoya disease and compared it with angiographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…However, these methods are associated with a limited availability and considerable radiation doses, which are of concern especially in a pediatric population potentially undergoing serial examinations. The more readily available option of CT perfusion imaging [23] is similarly limited in its use in children due to the radiation burden associated with the method. As a modality not associated with ionizing radiation, MRI has emerged as a valuable method for cerebral perfusion imaging in the assessment of children with moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods are associated with a limited availability and considerable radiation doses, which are of concern especially in a pediatric population potentially undergoing serial examinations. The more readily available option of CT perfusion imaging [23] is similarly limited in its use in children due to the radiation burden associated with the method. As a modality not associated with ionizing radiation, MRI has emerged as a valuable method for cerebral perfusion imaging in the assessment of children with moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the blood supply through collateral pathways can compensate for the reduced CBF, even with advancement of the disease. 1,18 However, CVR tends to diminish as MMD progresses. 18 We also found that the CBNS was related to impaired CVR, though not to cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Inability to compensate in times of stress can induce ischemia. In patients with stenotic lesions, baseline CTP maps are not useful in predicting cerebrovascular reserve; however, changes in CBF 60,62 and MTT 61 after acetazolamide challenge correlate with hemodynamic reserve (Fig 13). Acetazolamide is a potent carbonic anhydrase inhibitor causing short-term cerebral arteriole vasodilation except within territories that are already maximally dilated due to autoregulatory reflex vasodilation.…”
Section: Assessing Cerebrovascular Reservementioning
confidence: 99%
“…Collateral circulation plays an important role in the case of chronic stenoses. 60 Autoregulatory reflex vasodilation tends to be more important in cases of acute stenoses. 61 These mechanisms provide physiologic reserve to compensate during times of stress.…”
Section: Assessing Cerebrovascular Reservementioning
confidence: 99%